Liver transplantation for "very early" intrahepatic cholangiocarcinoma: International retrospective study supporting a prospective assessment. Issue 4 (24th August 2016) - Sapisochin, G.; Facciuto, M.; Rubbia‐Brandt, L.; Marti, J.; Mehta, N.; Yao, F.Y.; Vibert, E.; Cherqui, D.; Grant, D.R.; Hernandez‐Alejandro, R.; Dale, C.H.; Cucchetti, A.; et al.
Abstract : The presence of an intrahepatic cholangiocarcinoma (iCCA) in a cirrhotic liver is a contraindication for liver transplantation in most centers worldwide. Recent investigations have shown that "very early" iCCA (single tumors ≤2 cm) may have acceptable results after liver transplantation. This study further evaluates this finding in a larger international multicenter cohort. The study group was composed of those patients who were transplanted for hepatocellular carcinoma or decompensated cirrhosis and found to have an iCCA at explant pathology. Patients were divided into those with "very early" iCCA and those with "advanced" disease (single tumor >2 cm or multifocal disease). Between January 2000 and December 2013, 81 patients were found to have an iCCA at explant; 33 had separate nodules of iCCA and hepatocellular carcinoma, and 48 had only iCCA (study group). Within the study group, 15/48 (31%) constituted the "very early" iCCA group and 33/48 (69%) the "advanced" group. There were no significant differences between groups in preoperative characteristics. At explant, the median size of the largest tumor was larger in the "advanced" group (3.1 [2.5‐4.4] versus 1.6 [1.5‐1.8]). After a median follow‐up of 35 (13.5‐76.4) months, the 1‐year, 3‐year, and 5‐year cumulative risks of recurrence were, respectively, 7%, 18%, and 18% in the very early iCCA group versus 30%, 47%, and 61% in the advanced iCCA group, P = 0.01. The 1‐year, 3‐year, and 5‐year actuarial survival rates were, respectively, 93%, 84%, and 65% in the very early iCCA group versus 79%, 50%, and 45% in the advanced iCCA group, P = 0.02. Conclusion: Patients with cirrhosis and very early iCCA may become candidates for liver transplantation; a prospective multicenter clinical trial is needed to further confirm these results. (Hepatology 2016;64:1178‐1188)